The Human Epidermal Growth Factor Receptor 2 Screening Tests for Breast Cancer Suggested by the New Updated Recommendation of the American Society of Clinical Oncology/College of American Pathologists Will Involve a Rise of the In-Situ Hybridization Tests for the European Laboratories of Pathology. (22nd April 2014) - Garbar, Christian; Savoye, Aude-Marie; Mascaux, Corinne; Brabencova, Eva; Curé, Hervé
Abstract : Aims . The differences between the 2007 and the 2013 ASCO/CAP HER2 guidelines have been compared. We also discussed the potential consequences in our pathological practice. Material and Methodology . 189 HER2 fluorescence in situ hybridisation (FISH) tests were performed from 1016 preliminary HER2 immunohistochemical tests (IHC). All cases were reviewed and reclassed following the 2007 and 2013 ASCO/CAP recommendations. Results . The 2013 version decreased false-negative IHC (3/118 versus 1/54, P = n s ) and created more 2+ IHC (40/186 versus 89/186, P = 0 .001 ) or more 3+ IHC (9/186 versus 39/186, P = 0.001 ). One false-positive IHC was described for the 2013 version (0/9 versus 1/39, P = n s ). Equivocal FISH was reduced (8/186 versus 2/186, P = n s ). An estimation based on our data for 1000 patients showed a rise of our FISH tests for the control of 2+ IHC (180 tests for the 2007 version versus 274 tests for the 2013 version or FISH work overflow is +52%) and for the control of 2+/3+ IHC (300 for the 2007 version versus 475 for the 2013 version or FISH work overflow is +58%). Conclusions . The new 2013 ASCO/CAP guidelines have detected more HER2 positive cases but have increased the number of FISH tests.